2014
DOI: 10.1158/1541-7786.mcr-13-0668
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced CXCR4 Promotes Migration and Invasion of Ewing Sarcoma

Abstract: Ewing sarcoma is the second most common bone cancer in pediatric patients. Although the primary cause of death in Ewing sarcoma is metastasis, the mechanism underlying tumor spread needs to be elucidated. To this end, the role of the CXCR4/SDF-1a chemokine axis as a mediator of Ewing sarcoma metastasis was investigated. CXCR4 expression status was measured in primary tumor specimens by immunohistochemical (IHC) staining and in multiple cell lines by quantitative RT-PCR and flow cytometry. Migration and invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 40 publications
5
60
0
1
Order By: Relevance
“…In addition, we studied expression levels of the earlier reported CXCR4 isoforms in tumour samples as the expression of these isoforms in particular might partly be responsible for the contradictory results [15,16,20]. All chemokines and receptors of the CXCR4-CXCR7 axis were expressed in EWS but a large variation was observed between individual samples, consistent with previous observations [16,27]. The observed increased expression of CXCR7 and CXCL12 in tumour samples compared to cell lines could be stromal derived since both endothelial and perivascular cells express CXCR7 and CXCL12 and EWS is highly vascularised [28,29].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, we studied expression levels of the earlier reported CXCR4 isoforms in tumour samples as the expression of these isoforms in particular might partly be responsible for the contradictory results [15,16,20]. All chemokines and receptors of the CXCR4-CXCR7 axis were expressed in EWS but a large variation was observed between individual samples, consistent with previous observations [16,27]. The observed increased expression of CXCR7 and CXCL12 in tumour samples compared to cell lines could be stromal derived since both endothelial and perivascular cells express CXCR7 and CXCL12 and EWS is highly vascularised [28,29].…”
Section: Discussionsupporting
confidence: 80%
“…expression has been shown in EWS and this may hold for CXCR7 as well [27]. The local tumour microenvironment can be an influencing factor here as well.…”
mentioning
confidence: 69%
“…Previous reports have shown that the bone TME specifically promotes metastatic progression of Ewing sarcoma (9) and that its ability to grow in bone is dependent on the osteolytic phenotype (10). Moreover, a hypoxic microenvironment promotes activation of metastasis-associated gene expression in tumor cells and enhanced metastatic progression in xenograft models (11,12). In addition, gene expression profiling studies of primary localized tumor specimens demonstrated the important contribution of tumor stroma to relapse and patient survival (13).…”
Section: Introductionmentioning
confidence: 98%
“…Since hypoxia is also suitable to activate Rho-GTPases as part of the stress response, 38 this behavior may rely on a …”
mentioning
confidence: 99%